2009
DOI: 10.1007/s00259-008-1028-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion (HMPAO-SPECT) in patients with depression with cognitive impairment versus those with mild cognitive impairment and dementia of Alzheimer’s type: a semiquantitative and automated evaluation

Abstract: Automated analysis of HMPAO-SPECT data from MCI patients showed significant perfusion deficits in regions also involved in DAT patients, but ROC analysis demonstrated only moderate sensitivity and specificity for differentiating DAT patients from controls and DCI patients. Frontal hypoperfusion seems to correspond with conversion from MCI to DAT. Finally, the results in DCI patients again raise the question of depression as an early symptom of neurodegeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 52 publications
1
29
0
1
Order By: Relevance
“…We hypothesize that this compromised neurovasculature, together with widespread fibrin deposition, might lead to deficits in cerebral blood flow in these mice. Since hypoperfusion can lead to cognitive decline [36, 37], our current findings support our previous report that plg−/− mice exhibit memory deficits [5]. Our results also correlate well with what is observed in chronic neurodegenerative diseases in humans, such as MS and AD.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We hypothesize that this compromised neurovasculature, together with widespread fibrin deposition, might lead to deficits in cerebral blood flow in these mice. Since hypoperfusion can lead to cognitive decline [36, 37], our current findings support our previous report that plg−/− mice exhibit memory deficits [5]. Our results also correlate well with what is observed in chronic neurodegenerative diseases in humans, such as MS and AD.…”
Section: Discussionsupporting
confidence: 92%
“…Studies on postmortem tissue from these patients often show reduced neurovascular integrity and leakage of fibrin into the brain parenchyma [13]. AD and MS patients also present with hypoperfusion [37, 38], which could ultimately lead to their cognitive deficits. Future studies that examine the role of plasmin in neurodegenerative disease pathophysiology may be warranted as plasmin may have a significant impact on neurovascular integrity.…”
Section: Discussionmentioning
confidence: 99%
“…One previous SPECT study found that patients with aMCI showed hypometabolism in the frontal and subcortical areas and their abnormal social behaviors may be attributed to the impaired frontalsubcortical circuits [31]. Furthermore, [32] these studies also found that frontal cortical In our study, the loss of gray matter volume and reduction of ALFF were observed in the superior temporal gyrus and insula, which is consistent with the Xenon-enhanced computed tomography PET study [33]. A previous PET study also suggested that loss of metabolism also occurs at these two regions in the prodromal stage of AD [34].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the significance of abnormalities in MCI, usually defined as subjective and objective cognitive impairment without functional impairment, are difficult to assess: unless brains come to pathological examination shortly after the scan, intervening illness is likely to blur the picture. At best, patterns of hypoperfusion in MCI patients that are typical of AD will predict later conversion to dementia [56][57][58][59]. Of greatest interest is, of course, whether imaging can inform treatment decisions.…”
Section: Sensitivity and Specificitymentioning
confidence: 99%